ANALISIS YURIDIS JUAL BELI TANAH DENGAN HAK MEMBELI KEMBALI YANG DIDAHULUI DENGAN PERJANJIAN PINJAM MEMINJAM SECARA LISAN (STUDI PUTUSAN MAHKAMAH AGUNG RI NO. 317 K/PDT/2020) - Nirmansyah, Sandy; Yuyut Prayuti, Yuyut Prayuti; Arman Lany, Arman Lany (Program Studi Magister Ilmu Hukum Universitas Islam Nusantara, 2024)
The purpose of this writing is to find out and analyze the sale and purchase of land with the right to repurchase and to find out and analyze the Supreme Court Cassation Decision No. 317 K/Pdt/2020, which recognizes buying and selling with the right to repurchase which is preceded by an oral loan. The research method used by the author is a normative research method, with a statutory regulation approach and a conceptual approach, and the data collection techniques used are literature study and interviews, with the research location at the Bale Bandung District Court Class I A. From the results of this research It was found that the sale and purchase of land with the right to repurchase, which is preceded by a loan or loan, is prohibited in judicial practice. The Supreme Court Cassation Decision No. 317 K/Pdt/2020, dated 26 March 2020, which granted the Plaintiff's claim, as well as legitimizing the sale and purchase with the right to repurchase, is a decision that lacks legal considerations, falls into the category of Onvoldoende Gemotiverd decisions, because it does not take into account other legal facts, such as the Plaintiff's admission that PPJB Deed no. 1064/2018, dated 18 April 2016, was made on the basis of a loan and loan between the Plaintiff and the Defendant